2020
DOI: 10.1302/0301-620x.102b9.bjj-2019-1742.r1
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness assessment of dual-mobility bearings in revision hip arthroplasty

Abstract: Aims The rate of dislocation when traditional single bearing implants are used in revision total hip arthroplasty (THA) has been reported to be between 8% and 10%. The use of dual mobility bearings can reduce this risk to between 0.5% and 2%. Dual mobility bearings are more expensive, and it is not clear if the additional clinical benefits constitute value for money for the payers. We aimed to estimate the cost-effectiveness of dual mobility compared with single bearings for patients undergoing revision THA. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
(35 reference statements)
1
16
0
Order By: Relevance
“…One-year cycles were considered a realistic clinical period in which revisions are likely to occur, based on previous publications. 22,25 The model assumes that not all dislocations will result in revision surgery; rather, a proportion of patients would be successfully managed by closed reduction. 19,26 Patients undergoing revision surgery will remain at risk of a subsequent revision (re-revision).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One-year cycles were considered a realistic clinical period in which revisions are likely to occur, based on previous publications. 22,25 The model assumes that not all dislocations will result in revision surgery; rather, a proportion of patients would be successfully managed by closed reduction. 19,26 Patients undergoing revision surgery will remain at risk of a subsequent revision (re-revision).…”
Section: Methodsmentioning
confidence: 99%
“…Previously published evidence on the cost-effectiveness of DM-THA has been limited to primary THA for arthritis, 20 inclusive of all indications for THA 21 or limited exclusively to revision THA. 22,23 The purpose of this study is to assess the cost-effectiveness of DM-THA compared with SB-THA among adult patients with displaced hip fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Dual mobility cups provide a greater range of motion, a greater head-to-neck ratio, and a greater jump distance, resulting in a lower risk of instability [ 102 , 103 ]. Dual-mobility cups decrease the rate of dislocation in primary and revision THA [ 104 ]. Concerns with dual-mobility cups include increased wear and intra-prosthetic dislocation [ 105 ].…”
Section: Implants In Tha – Martin Thalermentioning
confidence: 99%
“…Furthermore, dual mobility bearings constitute a reliable treatment option to enhance hip stability and appear to have been widely adopted in THA in dysplastic patients and revision THA for instability [ 4 ]. As well as this, a recent cost-effectiveness analysis, utilising a Markov model in patients undergoing revision THA has shown that dual mobility implants in patients under 75 are cost-saving [ 5 ]. It has been suggested that the systematic use of dual mobility cups may induce substantial cost-savings compared to THA with a fixed bearing, even in primary THA [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of inexpensive spacers has been reported to give similar function and satisfaction as the use of an endoprosthesis. 32,33 With healthcare systems worldwide under pressure due to costconstraints, 34,35 surgeons must be able to justify using costly endoprostheses to provide optimal function over a considerable period of time.…”
mentioning
confidence: 99%